PROBLEM-BASED MODULE VALIDATION FOR COMPLEX PROCEDURE TEXT (VALIDASI MODUL BERBASIS MASALAH UNTUK TEKS PROSEDUR KOMPLEKS) - Rina Sartika (Universitas PGRI Sumatera Barat, 2020)
This research was conducted to overcome the limitations of teaching materials in complex text learning procedures. Students needed teaching materials in the form of learning modules as one source of learning. The data analysis technique was descriptive statistics to get the percentage of validity, practicality, and effectiveness of the learning module. The resulting data was displayed in the form of tables and histograms. The results of the study explained that the problem-based complex procedure text learning module is valid in terms of content. Language, presentation, and graphics with a percentage of 94.92% with a very valid category of problem-based text learning procedures in complex procedures. Based on the results of the study, it is concluded that the problem-based complex procedure text learning module developed is valid. This module can be used to overcome the limitations of teaching materials in complex text learning procedures.